1996
DOI: 10.1097/00007890-199601150-00004
|View full text |Cite
|
Sign up to set email alerts
|

The ??-1,3-Galactosyltransferase Knockout Mouse

Abstract: Organ xenografts in discordant combinations such as pig-to-man undergo hyperacute rejection due to the presence of naturally occurring human anti-pig xenoantibodies. The galactose alpha(1,3)-galactose epitope on glycolipids and glycoproteins is the major porcine xenoantigen recognized by these xenoantibodies. This epitope is formed by alpha(1,3)-galactosyltransferase, which is present in all mammals except man, apes, and Old World monkeys. We have generated mice lacking this major xenoantigen by inactivating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(81 citation statements)
references
References 21 publications
3
76
0
Order By: Relevance
“…Southern blot and sequencing analysis of DNA samples from all five piglets confirmed the targeted disruption of the first allele of the α1,3GT gene and the T-to-G point mutation in the second base of exon 9 in the second allele of the α1,3GT gene. It has been reported that α1,3GT DKO mice developed cataracts at 4 to 6 weeks of age (17). Physical examination of the four piglets at 7 weeks of age did not reveal any abnormalities or cataracts.…”
mentioning
confidence: 72%
“…Southern blot and sequencing analysis of DNA samples from all five piglets confirmed the targeted disruption of the first allele of the α1,3GT gene and the T-to-G point mutation in the second base of exon 9 in the second allele of the α1,3GT gene. It has been reported that α1,3GT DKO mice developed cataracts at 4 to 6 weeks of age (17). Physical examination of the four piglets at 7 weeks of age did not reveal any abnormalities or cataracts.…”
mentioning
confidence: 72%
“…That loss of the GGTA1 gene can be deleterious has become evident by the production of GGTA1 KO mice and pigs for xenotransplantation research (21,22,44). Animals with GGTA1 KO have both subtle and conspicuous health abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Additional manipulation(s) may be a prerequisite to enhance the expression of A and B antigens. These may include the knockout of the ␣1,3-galactosyltransferase gene (44) or the introduction of the ␣1,2-fucosyltransferase gene under strong promoter (45) to either abolish or lessen the expression of the ␣1,3-galactosyltransferase. These mice with different ABO phenotypes in the same genetic background may clarify the functionality of the ABO system in the future.…”
Section: Musculus Domesticusmentioning
confidence: 99%